On the use of the classical numerical methods for differential delay equations - Meilūnas, Mečislovas; Rumšiene, Rūta (Mathematical Modelling and Analysis, 1997)
An algorithm for the evaluatinion of discontinuity jumps in the DDE initial value problem is presented. That enables the use of the classical numerical methods for DDE initial value problem.First Published Online: 14 Oct 2010